2018
DOI: 10.1371/journal.pone.0190771
|View full text |Cite
|
Sign up to set email alerts
|

Structural validation of the Self-Compassion Scale with a German general population sample

Abstract: BackgroundPublished validation studies have reported different factor structures for the Self-Compassion Scale (SCS). The objective of this study was to assess the factor structure of the SCS in a large general population sample representative of the German population.MethodsA German population sample completed the SCS and other self-report measures. Confirmatory factor analysis (CFA) in MPlus was used to test six models previously found in factor analytic studies (unifactorial model, two-factor model, three-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 60 publications
6
55
1
Order By: Relevance
“…The CSR component clearly reflects protective mechanisms, but the USR component unambiguously represents features of vulnerability (Muris and Petrocchi 2017), which of course is difficult to reconcile with the premises of a positive psychology construct. The present study adds further evidence showing that CSR and USR are quite different in nature (see also Brenner et al 2017Brenner et al , 2018Coroiu et al 2018;Lopez et al 2018;Muris et al 2018;Neff et al 2018b). That is, as anticipated, compassionate self-responding was positively related to positive cognitive reactions, whereas uncompassionate selfresponding was mainly positively associated with negative cognitive reactions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The CSR component clearly reflects protective mechanisms, but the USR component unambiguously represents features of vulnerability (Muris and Petrocchi 2017), which of course is difficult to reconcile with the premises of a positive psychology construct. The present study adds further evidence showing that CSR and USR are quite different in nature (see also Brenner et al 2017Brenner et al , 2018Coroiu et al 2018;Lopez et al 2018;Muris et al 2018;Neff et al 2018b). That is, as anticipated, compassionate self-responding was positively related to positive cognitive reactions, whereas uncompassionate selfresponding was mainly positively associated with negative cognitive reactions.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, compassionate and uncompassionate selfresponding components in the SCS have been demonstrated to relate in a different way to external constructs (e.g., Brenner et al 2017;Brenner et al 2018;Coroiu et al 2018;Lopez et al 2018;Neff et al 2018aNeff et al , 2018b. This can be linked to Gilbert's (2000) Theory of Social Mentalities, which proposes that there are two distinct but related processing systems that underlie people's patterns of cognition, affect, and behavior in response to interpersonal challenges: the safeness system and the threat-defense system.…”
mentioning
confidence: 99%
“…However, there has been more research investigating the factor structure of the SCS, and the outcomes have been mixed: quite a number of studies obtained support for a correlated six-factor model (Benda and Reichova 2016;Castilho et al 2015;Cunha et al 2016;Garcia-Campayo et al 2014;Hupfeld and Ruffieux 2011;Kotsou and Leys 2016;Kumlander et al 2018;Petrocchi et al 2014;Pfattheicher et al 2017;Ursic et al 2019) while there are also other investigations pointing in the direction of a solution with two overarching factors representing compassionate and uncompassionate self-responding (Brenner et al 2017;Coroiu et al 2018;Costa et al 2016;Halamova et al 2018;Hayes et al 2016;Zhang et al 2019). Taken together, it can be concluded that the exact factor structure of the SCS is far from clear and tends to differ across studies.…”
Section: A Scientific Smoke Curtain To Defend the Use Of The Scs Totamentioning
confidence: 99%
“…Items are rated on a 5-point Likert scale (1 indicates seldom/never and 5 almost always), with higher scores indicating more selfcompassion. Given the conflicting results in the literature concerning the amount of self-compassion facets (Coroiu et al 2018;Muris et al 2018;Neff et al 2018aNeff et al , b, 2017, we executed exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and exploratory structural equation modeling (ESEM) to detect the underlying structure for the Dutch version of the SCS (Neff and Vonk 2009). EFA suggested a two-factor model, whereas CFA results showed a non-sufficient fit of all models (i.e., one-factor, two-factor, six-factor, bifactor, two-bifactor).…”
Section: Self-compassionmentioning
confidence: 99%
“…In addition, it is important to distinguish positive and negative indicators of psychological functioning, as previous research found that associations of mindfulness and self-compassion with psychological functioning differ when distinguishing positive and negative psychological outcomes (López et al 2016). Second, given the current debate about the number of facets of self-compassion (Coroiu et al 2018;Kumlander et al 2018;Muris et al 2018;Neff et al 2018aNeff et al , b, 2017, selfcompassion total scores as well as distinct facets need to be taken into account. That is, with respect to self-compassion, several studies have recently suggested a two factor model (instead of the original six facets), distinguishing a positive self-compassion factor (i.e., a combination of self-kindness, common humanity, mindfulness) and a negative selfcompassion factor (i.e., a combination of Self-judgment, Isolation, Mindfulness, Over-identification) (Costa et al 2016;López et al 2015;Petrocchi et al 2014).…”
mentioning
confidence: 99%